BALANCING NATIONAL SECURITY AND MIGRANT RIGHTS IN INTERNATIONAL LAW - Khakberdiev Mukhammad (Antis Publisher, 2024)
This article examines the complex intersection between national security and migrant rights within the framework of international law. With an increasing focus on security, many states have adopted policies that restrict migration, often infringing on human rights, particularly the rights of asylum seekers and refugees. Using data from various regions, including the United States, Europe, and Australia, the article analyzes the impact of securitization on migration policies, such as reduced asylum approval rates, the rise in migrant detentions, and violations of the non-refoulement principle. The research highlights the challenges in balancing state security with the protection of migrants, emphasizing the role of international organizations and legal frameworks in addressing these issues. The article concludes that while national security concerns are valid, states must uphold their international obligations to protect migrant rights.